SECTARIANISM IN ISLAM: THE STUDY OF KHAWARIJ AND MAJLIS MUJAHIDIN INDONESIA - Muhammad Sairi (Mimbar Agama Budaya, 2021)
Abstract. Basically, the study of sectarianism refers to the problem of understanding within a certain group, school, or belief. However, in its development this term has developed and is almost always associated with the study of the fanaticism of the madzhab (al-ta’asshubiyyah) and political partisans (al-hizbiyyah). Therefore, sectarianism as an ideology or ism often creates negative-destructive consequences, especially by creating a heroic attitude in defending the group as well as opposing other groups who are not in the same direction. In fact, not infrequently it creates radical attitudes on other parties in the name of the truth (read: religion) which they believe. This paper discusses sectarianism in Islam by using "multiple objects"; analysis of the Khawarij group as a portrait of classical sectarianism that had occurred in the early days of Islam as well as pulling it back to the present by analyzing the Majlis Mujahidin Indonesia (MMI) as a portrait of sectarianism that occurred in Indonesia in a modern context.. Abstrak. Pada dasarnya, kajian tentang sektarianisme merujuk pada persoalan sempalan paham dalam sebuah golongan, mazhab, maupun kepercayaan tertentu. Namun dalam perkembangannya istilah ini berkembang dan hampir selalu dikaitkan dengan kajian fanatisme madzhab (al-ta’asshubiyyah) dan partisan politik (al-hizbiyyah). Karena itu, sektarianisme sebagai sebuah paham atau isme seringkali memunculkan konsekuensi-konsekuensi negatif-destruktif terutama dengan memunculkan sikap heroik dalam membela kelompoknya sekaligus pertentangan kepada kelompok lain yang tidak searah. Bahkan tak jarang menimbulkan sikap-sikap radikal pada pihak lain atas nama kebenaran (baca: agama) yang diyakininya. Tulisan ini membahas tentang sektarianisme  dalam Islam dengan menggunakan “objek ganda”; analisa pada kelompok Khawarij sebagai potret sektarianisme klasik yang pernah terjadi pada masa-masa awal Islam sekaligus menariknya ke masa kini dengan menganalisa kelompok Majlis Mujahidin Indonesia (MMI) sebagai potret sektarianisme yang terjadi di Indonesia pada masa modern.